Penal fiscal liability of bailiff as the VAT payer - Fabian Nalikowski (Prawo Budżetowe Państwa i Samorządu, 2016)
This paper discusses the range and essence of penal fiscal liability court bailiff. The bailiffs being the VAT payers are required to calculate, collect and pay VAT on amount received from the sale of property in execution mode. Failure to comply with these obligations give rise to liability under the Polish Penal Fiscal Code. The degree of discomfort penalties and punitive measures depends on the amount of unpaid tax. The conviction and ruling of some punitive measures could give rise to dismissal from the function bailiff.